Abnormal bone growth and selective translational regulation in basic fibroblast growth factor (FGF-2) transgenic mice. - J. Douglas Coffin; Robert Z. Florkiewicz; Jon Neumann; T Mort-Hopkins; G W Dorn; P.S. Lightfoot; Rebecca Z. German; Philip N. Howles; Ann B. Kier; Barbara A. O’Toole (1995)
Basic fibroblast growth factor (FGF-2) is a pleiotropic growth factor detected in many different cells and tissues. Normally synthesized at low levels, FGF-2 is elevated in various pathologies, most notably in cancer and injury repair. To investigate the effects of elevated FGF-2, the human full-length cDNA was expressed in transgenic mice under control of a phosphoglycerate kinase promoter. Overexpression of FGF-2 caused a variety of skeletal malformations including shortening and flattening of long bones and moderate macrocephaly. Comparison by Western blot of FGF-2 transgenic mice to nontransgenic littermates showed expression of human FGF-2 protein in all major organs and tissues examined including brain, heart, lung, liver, kidney, spleen, and skeletal muscle; however, different molar ratios of FGF-2 protein isoforms were observed between different organs and tissues. Some tissues preferentially synthesize larger isoforms of FGF-2 while other tissues produce predominantly smaller 18-kDa FGF-2. Translation of the high molecular weight isoforms initiates from unconventional CUG codons and translation of the 18-kDa isoform initiates from an AUG codon in the FGF-2 mRNA. Thus the Western blot data from the FGF-2 transgenic mice suggest that tissue-specific expression of FGF-2 isoforms is regulated translationally.